Poetics of the proper name in three female authors of the Southern Cone: Somers, Eltit y Meruane (El Taco en la Brea, 2025)
The magical disposition of the proper name has been based throughout history on the belief in the essential link between name and referent. It is no coincidence that the plautine phrase popularized as nomen est omen: «Name is destiny», acquires fame in the Latin literary tradition. Although this essential and mythical power of the proper name weakened and diminished over the centuries, it did not disappear completely. After exploring the magical disposition of the name based on the Greco-Latin tradition, the customs of certain native peoples, and certain religious discourses, this article aims to address the contemporary modulation of magic in the nominal poetics of some texts by writers from the Southern Cone: Armonía Somers, Diamela Eltit and Lina Meruane. The hypothesis is that this contemporary magical tenor promotes specific performances of the name or nominal supplement that reactivate the augural-ominal aspects. These are organized within the sphere of nominal aesthetics, under the modulations of paradox, and parody, which without canceling the magical component, add complexity to it.
Keywords: proper name; nominal magic; literature studies; nominal poetics; Southern Cone